Learner operation algorithm development with model of requirements elicitation to software - Кунгурцев, Алексей Борисович; Калинина, София Александровна (Technology audit and production reserves, 2014)
The article is devoted to modeling the process of requirements elicitation to software. The authors argue that the problem of IT analysts’ training is topical, and offer their own development as a solution. The process model of requirements elicitation is given in the article and it is demonstrated the algorithms by which the worker with models can examine this process. It is determined the evaluation technology of all learner actions, which were made at each time point. The authors consider the number and quality of the collected requirements in evaluating and monitor all learner activity. Process model of requirements elicitation has been implemented in the simulator. Using a simulator for learner training in the control group shows a knowledge quality improvement. This model can be adapted to different subject areas and demonstrates the effectiveness of IT analysts’ training.